2019
DOI: 10.3390/mi10040271
|View full text |Cite
|
Sign up to set email alerts
|

Defining Cell Cluster Size by Dielectrophoretic Capture at an Array of Wireless Electrodes of Several Distinct Lengths

Abstract: Clusters of biological cells play an important role in normal and disease states, such as in the release of insulin from pancreatic islets and in the enhanced spread of cancer by clusters of circulating tumor cells. We report a method to pattern cells into clusters having sizes correlated to the dimensions of each electrode in an array of wireless bipolar electrodes (BPEs). The cells are captured by dielectrophoresis (DEP), which confers selectivity, and patterns cells without the need for physical barriers or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…[5][6][7][8][9][10] Their ability to modulate local electric fields lends them to the manipulation of cells and to the enrichment and separation of analytes. [11][12][13][14][15][16][17] And finally, by virtue of the polar and often graded profile of the interfacial potential across BPEs, they provide a platform for synthesis of Janus particles, useful as sensors and as microswimmers, [18][19][20][21][22] and other materials with compositional gradients. 23,24 BPEs are particularly well-suited to analytical challenges that demand multiplexing or amenability to point-of-need (PON) application because even large arrays of BPEs can be controlled with simple equipment, yet yield quantitative information about a system.…”
Section: Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10] Their ability to modulate local electric fields lends them to the manipulation of cells and to the enrichment and separation of analytes. [11][12][13][14][15][16][17] And finally, by virtue of the polar and often graded profile of the interfacial potential across BPEs, they provide a platform for synthesis of Janus particles, useful as sensors and as microswimmers, [18][19][20][21][22] and other materials with compositional gradients. 23,24 BPEs are particularly well-suited to analytical challenges that demand multiplexing or amenability to point-of-need (PON) application because even large arrays of BPEs can be controlled with simple equipment, yet yield quantitative information about a system.…”
Section: Referencesmentioning
confidence: 99%
“…Our group has also demonstrated that BPE length and shape, along with other variables, can be used to control the number of cells captured at BPE tips. 11 For these reasons, BPEs provide a convenient means by which to define parallel or serial dielectrophoretic capture points.…”
Section: Dielectrophoretic Techniques Using Bpesmentioning
confidence: 99%
See 1 more Smart Citation
“…BPEs have found application in many areas including electrochemical imaging, 1 electrokinetic separations, 2-5 materials synthesis, 6,7 electrocatalyst screening, 8 micromotors, 9,10 singlecell analysis, [11][12][13] visual voltammetry, 14,15 point-of-care sensing 16 and biosensing. 17 Recent advancements in bipolar electrochemical methods of analysis are discussed in a recent review by Rahn et al 18 A BPE comprises a conductor immersed in an electrolyte solution.…”
Section: Introductionmentioning
confidence: 99%
“…Lo and Lei [4] showed a simple flow-through device for continuous and massive lysis of cells via electricity. Banovetz et al [5] reported a method that uses an array of wireless bipolar electrodes to pattern cells into clusters.…”
mentioning
confidence: 99%